2020
DOI: 10.4160/23096586rtbwp20212
|View full text |Cite
|
Sign up to set email alerts
|

The tricot citizen science approach applied to on-farm variety evaluation: methodological progress and perspectives

Abstract: The tricot citizen science approach applied to on-farm variety evaluation: methodological progress and perspectives Published by the CGIAR Research Program on Roots, Tubers and BananasThe CGIAR Research Program on Roots, Tubers and Bananas (RTB) is a partnership collaboration led by the International Potato Center implemented jointly with the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT), the International Institute of Tropical Agriculture (IITA), and the Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The varieties were developed using feedback from cassava end users including participatory processing 21 and Tricot on-farm testing. 22…”
Section: Trials Compositionmentioning
confidence: 99%
“…The varieties were developed using feedback from cassava end users including participatory processing 21 and Tricot on-farm testing. 22…”
Section: Trials Compositionmentioning
confidence: 99%
“…The PL, having read about the triadic comparison of technologies (“tricot”) approach to on-farm trials ( van Etten et al, 2019 ), worked with the gender researcher and other members of the breeding team to develop a revised trial protocol. Building on previous experiences in participatory variety selection, the tricot approach engages a large number of “citizen scientists” to evaluate technologies under representative crop management conditions chosen by the farmer, using incomplete blocks of three varieties, with digital support throughout the process ( van Etten et al, 2020 ). This approach minimizes researcher control, allows farmers with limited land to participate, and enables participants to test technologies on land they know well and make observations throughout the season.…”
Section: Details: Seed Production Technology For Africa Projectmentioning
confidence: 99%
“…Several studies have proposed using environmental covariates to account for genotype × environment interaction in the analysis of multienvironment trials (Piepho et al, 1998;van Eeuwijk et al, 1996). Predictions of genotype performance at new locations are less common, but recent studies have demonstrated its feasibility (Buntaran et al, 2021;van Etten, de Sousa, et al, 2019).…”
Section: Predictions Of Genotype Performancementioning
confidence: 99%
“…The use of rankings implies an inherent loss of information when compared to measurements in a continuous scale using specialized instruments (Coe, 2002). However, collecting data in ranking format allows the participation of a larger number of farmers and a reduction in the costs of the experiments compared with other participatory methods (Coe, 2002;van Etten et al, 2020). Since the data are in ranking format, it should be analyzed with an appropriate statistical model such as the Plackett-Luce model (Luce, 1959;Plackett, 1975).…”
Section: Introductionmentioning
confidence: 99%